Effect of corporate social responsibility performance on dividend pay-out: Role of corporate governance quality - Maqbool, Zahid; Abid, Ammar; Bhutta, Aamir Inam (Frontiers in Psychology, 2022)
The study's goal is to analyze the influence of corporate social responsibility on dividend pay-out while considering the role of corporate governance quality on 185 mutual funds operating in Pakistan. This study used a two-step system called the Generalized Method of Moments to control not only endogeneity problems caused by inclusion of firm-specific variables, but also the endogeneity caused by dividend pay-out selection. According to findings, mutual funds that engage in higher levels of corporate social responsibility pay greater dividends. The quality of company governance has not only strong favorable impact on mutual fund dividend pay-outs, but also moderates the association between dividend pay-out and corporate social responsibility. Furthermore, differences exist among socially responsible Islamic and Conventional mutual funds in terms of dividend pay-out policy. These findings imply that quality of company governance performs a substantial role in dividend decisions. Policymakers and regulators should also encourage asset management firms to improve corporate governance quality and engage in more socially responsible activities, which can lead to improved fund performance and dividend pay-out.